Vision Performance of a 3-Zone Progressive™ Design Kalifilcon A Silicone Hydrogel Multifocal Contact Lens is Not Influenced by Pupil Size: Findings from a Multicenter Clinical Study - Phatak NR; Reindel W; Rah MJ; Proskin H; Giedd K; Pucker AD (Clinical Optometry, 2025)
Nitasha R Phatak,1 William Reindel,1 Marjorie J Rah,1 Howard Proskin,2 Kerry Giedd,3 Andrew D Pucker4 1Bausch + Lomb Incorporated, Rochester, NY, USA; 2Howard M. Proskin & Associates, Rochester, NY, USA; 3Eola Eyes, Orlando, FL, USA; 4Lexitas Pharma Services, Inc., Durham, NC, USACorrespondence: Marjorie J Rah, Bausch + Lomb Incorporated, 1400 N. Goodman St, Rochester, NY, 14609, USA, Tel +1 585-413-6397, Email marjorie.rah@bausch.comPurpose: Factors including age, refractive error, and luminance can affect pupil size and may influence the performance of multifocal contact lenses (MFCLs). This post-hoc analysis aimed to investigate correlations between pupil size and vision performance of a 3-Zone Progressive™ design, daily disposable silicone hydrogel (kalifilcon A) MFCL.Methods: Habitual MFCL wearers aged ≥ 40 years were enrolled in a 3-week, single-arm, bilateral, open-label study to assess near, intermediate, and distant vision performance. Pupil sizes were recorded at dispensing, along with binocular high-contrast visual acuity (VA) by logMAR. VA was assessed at 1- and 3-weeks’ follow-up for distance, intermediate, and near vision, and participants rated vision performance using a 0– 100 scale (100=most favorable) at both these follow-ups. Responses with score ≥ 50 were considered favorable. Pearson correlation coefficient (r) was used to determine the correlation significance.Results: Pupil size ranged from 2.0 mm to 7.0 mm. Mean logMAR VA was − 0.009, 0.046, and 0.114 (1 week), and − 0.012, 0.046, and 0.115 (3 weeks) for distance, intermediate, and near vision, respectively. Statistical analysis of the VA distribution found no significant correlation between VA and pupil size after 1 week of MFCL wear for distance or near vision (r2=0.003 and 0.006, respectively; both p≥ 0.05), and a weak but statistically significant correlation between intermediate VA and pupil size (r2=0.017; p< 0.05). No correlations were observed after 3 weeks for any distance (all p≥ 0.05). Participants rated subjective vision highly (84.0± 19.9, 89.2± 11.8, and 82.5± 18.5, respectively at 1 week, and 84.6± 18.0, 89.3± 12.6, and 84.2± 17.9, respectively at 3 weeks). Responses were favorable at both visits (p< 0.05). Correlations between vision rating and pupil size were not significant at either visit (p≥ 0.05).Conclusion: The kalifilcon A daily disposable silicone hydrogel MFCL delivers stable VA and significantly favorable (p< 0.05) ratings at all distances for patients with a wide range of pupil sizes.Keywords: presbyopia, visual acuity, progressive multifocal design, contact lens